Anti-tissue transglutaminase antibodies (TG2A) positivity and the risk of vitamin D deficiency among children - a cross-sectional study in the generation R cohort - Laura A. van der Velde; Sanne A. Beth; Trudy Voortman; Menno C. van Zelm; Henriette A. Moll; Jessica C. Kiefte-de Jong (BMC, 2023)
Abstract Background Suboptimal vitamin D status is common in people with celiac disease (CeD), a disease that can be characterized by the presence of serum anti-tissue transglutaminase antibodies (TG2A) (i.e., TG2A positivity). To date, it remains unclear whether childhood TG2A positivity is associated with vitamin D status and how this potential association can be explained by other factors than malabsorption only, since vitamin D is mainly derived from exposure to sunlight. The aim of our study was therefore to assess whether childhood TG2A positivity is associated with vitamin D concentrations, and if so, to what extent this association can be explained by sociodemographic and lifestyle factors. Methods This cross-sectional study was embedded in the Generation R Study, a population-based prospective cohort. We measured serum anti-tissue transglutaminase antibodies (TG2A) concentrations and serum 25-hydroxyvitamin D (25(OH)D) concentrations of 3994 children (median age of 5.9 years). Children with serum TG2A concentrations ≥ 7 U/mL were considered TG2A positive. To examine associations between TG2A positivity and 25(OH)D concentrations, we performed multivariable linear regression, adjusted for sociodemographic and lifestyle factors. Results Vitamin D deficiency (serum 25(OH)D < 50 nmol/L) was found in 17 out of 54 TG2A positive children (31.5%), as compared to 1182 out of 3940 TG2A negative children (30.0%). Furthermore, TG2A positivity was not associated with 25(OH)D concentrations (β -2.20; 95% CI -9.72;5.33 for TG2A positive vs. TG2A negative children), and this did not change after adjustment for confounders (β -1.73, 95% CI -8.31;4.85). Conclusions Our findings suggest there is no association between TG2A positivity and suboptimal vitamin D status in the general pediatric population. However, the overall prevalence of vitamin D deficiency in both populations was high, suggesting that screening for vitamin D deficiency among children, regardless of TG2A positivity, would be beneficial to ensure early dietary intervention if needed.